Using dated molecular phylogenies to help reconstruct geological, climatic, and biological history: Examples from Colombia (2018)
Attempts at historical reconstruction are based on limited data. We are more likely to produce accurate historical reconstructions by utilizing information from diverse sources and pooling data within the relevant research communities which will allow us to build up a moving picture of the geological, climatic, and biological evolution of our planet. We suggest that dated phylogenies of plants can contribute greatly to a better understanding of Earth history. Timing of phylogenetic splits of lowland restricted lineages on either side of the Andes could provide information on the timing of montane uplift and associated climatic changes. The timing of the arrival and diversification of organisms restricted to specific climatic regimes at a particular altitude can provide information on the age at which mountains reached a height adequate for that climate once corrected for global climate changes. As a model for study, we discuss how dated phylogenies in biome rich Colombia may contribute to an understanding of geological and climatic change in north‐western South America. Lowland wet forest restricted lineages separated from the mid‐Miocene, whereas lineages primarily restricted to mid‐altitude cloud forests began to diversify from the mid‐ to late‐Miocene and the majority of high‐altitude Páramo lineages began to diversify during the Pliocene. The age of diversification of altitudinally restricted lineages therefore gives an indication of the age at which particular altitudes may have been reached.